Journalism and communication for risk managementin the Andean region: journalitics discourse for a preventive and prospective approach: Discursos periodísticos y perspectivas para un enfoque prospectivo y preventivo - Obregón, Rafael; Arroyave, Jesús; Barrios, Marta Milena (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
The following article analyses the journalistic discourses and the representation of key topics related to disaster risk management in four Andean countries. This study uses as a theoretical framework of media and journalistic research, such as Agenda Setting (journalistic agenda) and Framing, as well as key concepts on disaster risk management. The article focuses on: 1) how a group of Andean newspapers, on their online editions, approached and characterized risk management during the period April 2007 - July 2008; 2) the nature of the dominant journalistic discourses during that period; and 3) the implications of such discourses in the field of communication for disaster risk management. This article will provide empirical evidence to work as a common ground to guide future actions helping journalists and communicators to better inform the community about risk management.